Spontaneous avalanche ionization of a strongly blockaded Rydberg gas - Robert-de-Saint-Vincent, Martin; Hofmann, Christoph S.; Schempp, Hanna; Günter, Georg; Whitlock, Shannon; Weidemüller, Matthias (Physical review letters, 2013)
We report the sudden and spontaneous evolution of an initially correlated gas of repulsively interacting Rydberg atoms to an ultracold plasma. Under continuous laser coupling we create a Rydberg ensemble in the strong blockade regime, which at longer times undergoes an ionization avalanche. By combining optical imaging and ion detection, we access the full information on the dynamical evolution of the system, including the rapid increase in the number of ions and a sudden depletion of the Rydberg and ground state densities. Rydberg-Rydberg interactions are observed to strongly affect the dynamics of plasma formation. Using a coupled rate-equation model to describe our data, we extract the average energy of electrons trapped in the plasma, and an effective cross section for ionizing collisions between Rydberg atoms and atoms in low-lying states. Our results suggest that the initial correlations of the Rydberg ensemble should persist through the avalanche. This would provide the means to overcome disorder-induced heating, and offer a route to enter new strongly coupled regimes.